GC-MS analysis of the Phytocomponents in the plant extracts of Bitter Apple (Citrullus Colocynthis) and their Antibacterial activities against selected pathogenic and food spoilage microorganisms - Banjo T.T; Lateef E.O.; Malomo M.O; Chuba C.T (Covenant Journal of Physical and Life Sciences, 2022)
The antibacterial potency of the ethanolic and aqueous extracts of the seeds and fruit epicarp of Citrullus colocynthis was evaluated against Bacillus cereus, Pseudomonas aeruginosa and Staphylococcus aureus using agar-well diffusion method. GC-MS analysis and phytochemical screening of the ethanolic and aqueous extracts of the seeds and fruit epicarp were carried out. The ethanolic and aqueous extracts of the fruits of the bitter apple showed inhibitory activities against the test organisms with zones of inhibition ranging between 2 mm and 16 mm, However, the range of inhibition with the seed extract was 5 mm and 18 mm. The GC-MS analysis revealed a total of forty-four and forty-nine phyto-compounds in the extracts of fruits and seeds of C. colocynthis respectively. This study showed that ethanolic extracts of the seeds of bitter apple could be employed in the pharmaceutical industry as a potent antimicrobial agent in the formulation of drugs